Effect of Humic acid, Cytokinin and Arginine on Qualitative Traits and Yield of Bean Plant Phaseolus vulgaris L. Under Salt Stress - Sheyaa, Tabarak Abbas; F. Karomi Kisko , Mushtak (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2024)
To Investigate optimum growth and production under salinity, some materials have been added in sufficient quantities to obtain an ideal crop of salt sensitive bean plants. This experiment was conducted during the spring growing season in 2022 in the agricultural fields in Abu Ghraib, Baghdad governorate, to study the effects of humic acid, cytokinin, and arginine and their interaction on 6 parameters reflecting the total of quantitative and yield traits of bean plants var. Astrid (from MONARCH seeds, China). A factorial design with 3 replicates was used, the first factor included 3 groups of Humic acid; H0, H1 (6 Kg.h-1), and H2 (12 Kg.h-1). The second factor included 2 groups; C0 (spray distilled water), and C1 (100 mg.l-1 benzel adenine), and the third factor included 3 groups of Arginine; A0 (spray distilled water), A1 (100 mg.l-1), and A2 (200 mg.l-1). For humic acid, the results showed that H2 treatment caused the significantly highest values in all the studied traits, except for proline. Results of cytokinin treatment showed that C1 treatment led to significantly higher values in all the studied traits, except for proline. For arginine treatment, the results indicated that there was no significant difference between A1, and A2. For the binary overlap among treatments, the results showed the highest values were  H2C1, A2C1, and H2A2, except for chlorophyll content was H2A1. The H2A2C1 triple overlap treatment resulted in the highest values compared to all other treatments for all traits. It is evident that from the results, proline was the highest value in the control treatment of all traits. In conclusion, the present study found that humic acid, cytokinin, arginine and their interactions enhance significantly the quantitative traits and production of bean plants under salinity stress.